Collected Works of George Grant : Volume 1 (1933-1950) - Grant, George Parkin, 1918-1988 (Book collections on Project MUSE., 2000)
More than a decade after his death, George Grant continues to stimulate, challenge, and inspire. During his lifetime he influenced a broad cross-section of Canadians, urging them to think more deeply about matters of social justice and individual responsibility. He wrote on subjects as diverse as technology, abortion, Canadian politics and nationalism, and the war in Vietnam, and was claimed equally by rightist and leftist causes.Grant's legacy includes six books and more than two hundred articles, as well as numerous broadcast transcripts, extensive correspondence, and a wealth of unpublished lectures, essays, and notes. In this projected eight-volume series, Grant's published and unpublished writings, including his complete correspondence, will be brought together for the first time. The texts are annotated, and each volume includes an introduction to the period that it covers. The series will not only make it possible to see the whole pattern of Grant's thought, but will also invite a reconsideration of the nature and importance of his work.Volume I covers Grant's intellectual development through his student years. Included are his early reviews, a brief journal written as he recovered from tuberculosis in 1942, and his earliest social and political writings about Canadian and international affairs. The most important of Grant's formative years were those spent at Oxford after the war, culminating in the writing of his DPhil thesis on the Scottish philosopher John Oman. In this dissertation, published here in full, we see the main themes of Grant's thought worked out for the first time.